Government-driven social enterprises in South Korea: lessons from the Social Enterprise Promotion Program in the Seoul Metropolitan Government - Jung, Kyujin; Seo, Inseok; Jang, Hee Soun (2016)
Although scholars and practitioners in the field of public administration have investigated the nature of social enterprises emerging from the nonprofit sector, little research has been undertaken on the role of governments in facilitating prospective social enterprises to transform nonprofits into social enterprises. This research explores the global phenomenon of social entrepreneurship by analysing the government-driven social enterprise programs in South Korea. What is the government-driven social enterprise policy in South Korea? What is the role of the government in driving the success of the social enterprises in South Korea? What are the factors that affect the success of government-driven social enterprises? The results of this study highlight how government support helps nonprofit organizations cope effectively with diverse constraints that may cause nonprofit failure in societies like South Korea. The study findings confirm that Salamon's third-party government perspective and nonprofit failure theory justify government intervention, suggesting that governments may drive nonprofit organizations efficiently to overcome a propensity to failure by providing them with resources. - Reproduced.
Keywords: Nonprofit organizations